Process Optimization of Thawed Cloudy Huyou Juice Clarification Using a Composite of Carboxymethyl Chitosan and Sodium Alginate - Peichao Zhang; Liang Zhang; Xiayu Liu; Yuxi Wang; Jiatong Xu; Pengfei Liu; Boyuan Guan (Foods)
Cloudy huyou juice is increasingly popular for its unique flavor, but flocculent precipitation after cold storage and thawing affects its sensory quality and increases production costs. This study optimized the clarification of thawed cloudy huyou juice using a composite of carboxymethyl chitosan (CC) and sodium alginate (SA), prepared via ionic and covalent crosslinking. The composite was characterized by SEM, FTIR, and thermal analysis. Transmittance was used to evaluate clarification performance. The effects of dosage, adsorption time, and temperature were first assessed through single-factor experiments, followed by optimization using a Box–Behnken response surface methodology. The composite significantly improved clarity (p < 0.05), reaching 85.38% transmittance under optimal conditions: 22 mg dosage, 80 min time, and 38 °C. The composite dosage and temperature were the most influential factors. Reusability tests showed declining performance, with the transmittance dropping to 57.13% after five cycles, likely due to incomplete desorption of adsorbed compounds. These results suggest that the CC-SA composite is an effective and reusable clarifying agent with potential for industrial applications in turbid fruit juice processing.